Community-Based Fisheries Management: A Systematic Literature Review - Suprianto Suprianto; Umar Iskandar; Muh. Ersyad Indra Praja; Nur Mutmainna; Andi Fitriana; Resky Aprilia Farna HP (Jurnal Riset Diwa Bahari (JRDB), 2023)
Community-Based Fisheries Management (CBFM) has emerged as a widely adopted governance approach to promote sustainable fisheries, biodiversity conservation, and the socioeconomic well-being of coastal communities. Despite the growing body of literature on CBFM, a comprehensive synthesis of its development, dominant research themes, and future directions remains limited. This study aims to systematically review global research on Community-Based Fisheries Management by identifying publication trends, thematic evolution, governance approaches, implementation challenges, and emerging research opportunities. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure a transparent and rigorous article selection process. Relevant publications were retrieved exclusively from the Scopus database using predefined search criteria and analyzed through descriptive and bibliometric techniques. Bibliometric mapping was conducted using VOSviewer to visualize keyword co-occurrence, collaboration networks, and thematic clusters. The findings reveal a substantial increase in scholarly attention to CBFM over the last decade, with research concentrating on co-management, stakeholder participation, fisheries governance, marine conservation, livelihood sustainability, and adaptive resource management. Recent studies increasingly integrate climate change adaptation, ecosystem-based management, blue economy strategies, and social-ecological resilience into community-based fisheries governance. Nevertheless, persistent challenges remain, including institutional capacity, unequal stakeholder participation, policy fragmentation, limited financial resources, and conflicts over marine resource use. This review provides a comprehensive overview of the intellectual structure and evolution of Community-Based Fisheries Management research while identifying critical knowledge gaps and future research priorities. The findings contribute to the advancement of sustainable fisheries governance and offer valuable insights for researchers, policymakers, and practitioners seeking to strengthen community-centered approaches to marine resource management.